Effect of partial and complete replacement of fishmeal with mushroom stalk meal and soy bean meal on growth performance of Nile Tilapia, Oreochromis niloticus fingerlings - Hasniyati Muin; Norhidayah Mohd Taufek; Raji Ameenat Abiodun; Hanan Mohd Yusof; Shaharudin Abdul Razak (Universiti Kebangsaan Malaysia, 2015)
A dietary study was conducted to assess the use of mushroom stalk (MM), Pleurotus sajor caju, an agriculture waste and soy bean meal (SBM) as partial and complete replacement of fishmeal (FM) in tilapia fingerling diets. The study was conducted for 56 days. The diets were processed into sinking pellets. The experimental diets were formulated to replace fish meal protein at 0, 33, 67 and 100% (diet 4, 3, 2 and 1). In this experiment, Nile tilapia fingerlings weighing about 1.00 g were fed each of four isonitrogenous diet. They were randomly distributed into 12 plastic tanks with each tank stocking 20 fish. The experiment was conducted in three replicates for each treatment. All the diets were well accepted by the fish. No physical abnormalities were observed in all treatments. Good growth performance was shown in 33% replacement (diet 3) of FM diet. However, diet 1 (100% replacement) gave the highest increment in crude protein level and the best result of feed conversion ratio (FCR) and protein efficiency ratio (PER). Furthermore, the 100% replacement of FM (diet 1) was the best with a production cost of RM2.61/kg.